Literature at work: Zionist literary realism between utopia and "Khirbet Khizeh". Issue 1 (2nd January 2017) - Nir, Oded
ABSTRACT: Zionist Hebrew literary realism from the 1920s and 1930s is usually considered to be nothing but propagandistic literature, working in the service of national ideological imperatives. Challenging this literary-historical narrative, this essay argues that Zionist realist writers attempted to imagine radical collective transformation, which cannot be reduced to (and was at times at odds with) the subsequent establishment of the State of Israel. Emphasizing the formal similarities between Zionist realism and the structure of utopian novels, the essay suggests that the realists did not simply celebrate a Zionist metanarrative. Rather, realist works by Ever Hadani and Yisrael Zarchi thematize in a variety of ways the contradiction between emancipatory goals and the everyday realities of workers. The essay argues that S. Yizhar's "Khirbet Khizeh" should be read as expressing the crisis of the collective transformative project that animated the realists' literary imaginary. In this sense, Yizhar's novella signals the foreclosure of transformative possibilities in the late 1940s.